2022
DOI: 10.1177/21925682221087467
|View full text |Cite
|
Sign up to set email alerts
|

How Does Gravity Influence the Distribution of Lordosis in Patients With Sagittal Malalignment?

Abstract: Study Design Retrospective cohort study. Objective Compare the supine vs standing radiographs of patients with adult spinal deformity against ideals defined by healthy standing alignment. Methods 56 patients with primary sagittal ASD (SRS-Schwab Type N) and 119 asymptomatic volunteers were included. Standing alignment of asymptomatic volunteers was used to calculate PI-based formulas for normative age-adjusted standing PI–LL, L4–S1, and L1–L4. These formulas were applied to the supine and standing alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…While interpreting these findings, it is crucial to note that segmental lumbar lordosis measurements in supine and prone positions may not directly compare to those calculated from pre-operative standing radiographs. For instance, in a retrospective cohort study of 56 patients with sagittal malalignment, Fourman et al found that supine positioning improved distal lumbar lordosis but did not fully correct to age-matched norms, particularly in the proximal lumbar spine, indicating that gravity significantly influences lordosis distribution in patients with sagittal malalignment [ 27 ]. Furthermore, in a retrospective study of 63 patients, Benditz et al noted that standing radiographs typically showed slightly higher lordosis values compared to supine Magnetic Resonance Images (MRIs), especially at L5/S1, indicating that MRI can estimate global lumbar lordosis, but single-level lordosis should ideally be determined using standing radiographs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While interpreting these findings, it is crucial to note that segmental lumbar lordosis measurements in supine and prone positions may not directly compare to those calculated from pre-operative standing radiographs. For instance, in a retrospective cohort study of 56 patients with sagittal malalignment, Fourman et al found that supine positioning improved distal lumbar lordosis but did not fully correct to age-matched norms, particularly in the proximal lumbar spine, indicating that gravity significantly influences lordosis distribution in patients with sagittal malalignment [ 27 ]. Furthermore, in a retrospective study of 63 patients, Benditz et al noted that standing radiographs typically showed slightly higher lordosis values compared to supine Magnetic Resonance Images (MRIs), especially at L5/S1, indicating that MRI can estimate global lumbar lordosis, but single-level lordosis should ideally be determined using standing radiographs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Kim: Lumbar spine flexibility is key to evaluating adult spinal deformity [10,18,19] and predicting the usage for osteotomies to achieve the correct sagittal alignment during corrective surgery [12]. Flexibility of the lumbar spine can be identified using supine radiographs, in which the PI-LL mismatch will normalize compared with standing radiographs.…”
Section: Clinical Scenariomentioning
confidence: 99%